Affective Primacy vs. Cognitive Primacy: Dissolving the Debate - Lai, Vicky T.; Hagoort, Peter; Casasanto, Daniel (Frontiers in Psychology, 2012)
When people see a snake, they are likely to activate both affective information (e.g., dangerous) and non-affective information about its ontological category (e.g., animal). According to the Affective Primacy Hypothesis, the affective information has priority, and its activation can precede identification of the ontological category of a stimulus. Alternatively, according to the Cognitive Primacy Hypothesis, perceivers must know what they are looking at before they can make an affective judgment about it. We propose that neither hypothesis holds at all times. Here we show that the relative speed with which affective and non-affective information gets activated by pictures and words depends upon the contexts in which stimuli are processed. Results illustrate that the question of whether affective information has processing priority over ontological information (or vice versa) is ill posed. Rather than seeking to resolve the debate over Cognitive vs. Affective Primacy in favor of one hypothesis or the other, a more productive goal may be to determine the factors that cause affective information to have processing priority in some circumstances and ontological information in others. Our findings support a view of the mind according to which words and pictures activate different neurocognitive representations every time they are processed, the specifics of which are co-determined by the stimuli themselves and the contexts in which they occur.